Evaluating the suitability of policy instruments for urban flood risk reduction. Issue 2 (1st February 2020) - Henstra, Daniel; Thistlethwaite, Jason; Dordi, Truzaar
ABSTRACT: City governments have access to a range of policy instruments to reduce flood risk, but choosing among these tools is challenging. This article identifies fourteen different policy instruments that could contribute to urban flood risk reduction and draws on interviews with expert stakeholders to score these instruments across eight evaluation criteria. The results indicate which policy tools the interviewees consider to be most and least suitable and illuminate the trade-offs inherent in instrument selection. Complementary relationships between the various instruments are also considered in the context of instrument mixes – combinations of multiple policy tools designed to maximise urban flood risk reduction.